2012
DOI: 10.1002/ptr.3707
|View full text |Cite
|
Sign up to set email alerts
|

Myrislignan Attenuates Lipopolysaccharide‐induced Inflammation Reaction in Murine Macrophage Cells Through Inhibition of NF‐κB Signalling Pathway Activation

Abstract: Myrislignan is a new kind of lignan isolated from Myristica fragrans Houtt. Its antiinflammatory effects have not yet been reported. In the present study, the antiinflammatory effects and the underlying mechanisms of myrislignan in lipopolysaccharide (LPS)-induced inflammation in murine RAW 264.7 macrophage cells were investigated. Myrislignan significantly inhibited LPS-induced production of nitric oxide (NO) in a dose-dependent manner. It inhibited mRNA expression and release of interleukin-6 (IL-6) and tumo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 37 publications
0
19
0
Order By: Relevance
“…TNF‐α and IL‐1β are well‐known proinflammatory cytokines and play a crucial role in inflammation (Smith et al ., ). Plant‐derived compounds belonging to different chemical classes, such as polysaccharides (Yu et al ., ), terpenes (Ferrari et al ., ), phenols (Romano et al ., ), lignans (Jin et al ., ), saponins (Lai et al ., ), and flavonoids (Chao et al ., ) have been shown to inhibit nitric oxide production in macrophages. In this study, we initially suggested that the MeOH extract of D .…”
Section: Discussionmentioning
confidence: 99%
“…TNF‐α and IL‐1β are well‐known proinflammatory cytokines and play a crucial role in inflammation (Smith et al ., ). Plant‐derived compounds belonging to different chemical classes, such as polysaccharides (Yu et al ., ), terpenes (Ferrari et al ., ), phenols (Romano et al ., ), lignans (Jin et al ., ), saponins (Lai et al ., ), and flavonoids (Chao et al ., ) have been shown to inhibit nitric oxide production in macrophages. In this study, we initially suggested that the MeOH extract of D .…”
Section: Discussionmentioning
confidence: 99%
“…Flaxseed represents the highest source of dietary plant lignans, predominantly secoisolariciresinol diglucoside (SDG) (Kuijsten and others ). Flaxseed lignans are metabolized to mammalian lignans, primarily enterolactone (EL) and enterodiol (ED), by colonic microbiota (Duncan and others ), which exert biological activities such as anticancer (Danbara and others ; Qu and others ), antioxidative, antiestrogenic, and anti‐inflammatory activities (Kuijsten and others ; During and others ; Jin and others ). Flaxseed contains 20% to 28% dietary fibers, which have been associated with health benefits such as blood serum cholesterol reduction (Riccioni and others ; Satija and Hu ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, acute inflammation is essentially a beneficial process, particularly that which develops in response to infectious pathogens. Chronic inflammation, however, is an undesirable phenomenon and is involved in the pathogenesis of chronic diseases such as cancer, arthritis, autoimmune disorders, and vascular diseases [13]. For these reasons, research has focused on the control of inflammatory reactions.…”
Section: Introductionmentioning
confidence: 99%